Electronic sputtering of thin lithium fluoride films induced by swift heavy ions. (23rd July 2015) - Martinez, R; Langlinay, Th; Boduch, P; Cassimi, A; Hijazi, H; Ropars, F; Salou, P; da Silveira, E F; Rothard, H
Abstract: The sputtering of secondary ions from thin lithium fluoride films of different thickness (2 nm ≤  z  ≤ 106 nm) irradiated by swift heavy ions (Ni and Ge: ∼10 MeV/ u ) was studied under ultrahigh-vacuum conditions by a time-of-flight imaging technique ( XY -TOF-SIMS). Most of the positive ions emitted are (LiF) n Li + clusters. Cluster structure and stability (magic numbers) are analyzed. A pronounced dependence of sputtered particle yields on the film thickness z was observed. The onset of large cluster emission occurs at a thickness of about z  = 20 nm. For thinner films, z  = 2 and z  = 4 nm, only small clusters ( n  < 6) are ejected. A threshold for the emission of large clusters was also observed as a function of the electronic stopping power S e at around 6 keV nm −1 . This leads to the important conclusion that both a sufficient amount of material ( z -dependence) and of deposited energy ( S e -dependence) are needed for large ionic cluster emission to occur.